QUALITY ASSURANCE DIAGNOSTIC PROCEDURES WITHIN THE DOCTORAL SCHOOL OF THE UNIVERSITY OF PETROȘANI - CODRUŢA DURA; IMOLA DRIGĂ (Annals of the University of Petrosani: Economics)
The paper brings forward the quality procedures employed by The Doctoral School within a higher education institution from the South Western Region of Romania – the University of Petroșani. The above mentioned academic entity organizes doctoral studies since 1962 in four distinct fields: “Mines, Oil and Gases”, “Industrial engineering”, “Systems engineering” and “Engineering and management”. With 162 doctoral students and 23 scientific advisers in the academic year 2020-2021, The Doctoral School has developed and applied, over the last few years, a functional procedure regarding the internal evaluation and monitoring of the doctoral domains which envisages the following main dimensions: the scientific activity carried out by doctoral coordinators; the quality of infrastructure and logistics available for the research activity; the existence and the functionality of fundamental regulations on organizing and conducting the doctoral studies; the status of research activities undertaken by the doctoral students and the quality of social and support academic services. Following the permanent process of applying and monitoring such criteria, the quality of the didactic and research activities performed within the Doctoral School of University of Petroșani was acknowledged by the Ministry of Education and the Romanian Agency for Quality Insurance in Higher Education when assessing the institutional external evaluation in 2021.